Tantangan dan Solusi Guru dalam Evaluasi Pembelajaran Matematika di SMP untuk Mengukur Penilaian Autentik di Tengah Tekanan Waktu: Sebuah Systematic Literature Review - Syamsinar Syamsinar; Nur Syazwana; Dianti Hijaya (Journal of Mathematics, Statistics and Applications, 2025)
This study aims to analyze the challenges and solutions faced by teachers in implementing authentic assessment in junior high school mathematics learning amidst time constraints, administrative burdens, and curriculum demands. Using a Systematic Literature Review (SLR) approach, 12 studies published between 2020 and 2025 were analyzed, consisting of eight studies in Indonesia and four studies in Southeast Asia and internationally. The study results indicate that the implementation of authentic assessment is hampered by teachers' low skills in designing valid rubrics, excessive administrative burdens, and pressure to achieve curriculum targets, which makes teachers tend to revert to using conventional tests. However, the literature also highlights several solutions, including the use of digital technologies such as Learning Management Systems (LMS) and rubric generators, ongoing teacher training and workshops, and collaboration through peer assessment to streamline the evaluation process. This study recommends that schools and policymakers reduce non-teaching administrative burdens, provide regular professional training, and develop practical and flexible assessment guidelines to support the sustainable and effective implementation of authentic assessment in mathematics learning.